Tourists’ intention in selection of a restaurant: testing a mediating influence of perception - Rahman, Muhammad Sabbir; Abdullah, Muhammad Madi; AbdelFattah, Fadi AbdelMuniem; Moudud, Hasan (2015)
The purpose of this research is to inspect in what extent service quality and satisfaction influence the purchase intention from a restaurant when perception employed as a mediating function. In order to test the proposed conceptual framework, this research used a sample of 200 tourists’ who visited Kuala Lumpur, Malaysia. This research included both domestic and international tourists. Apart from confirmatory factor analysis, this research applied structural equation modeling to test the hypothesis. The results show that the relationships among the variables are all significant. Moreover, the mediating effect of perception in between service quality and purchase intention is partial. On the other hand, the role of perception as a mediation in between the relationship of tourists’ satisfaction and their purchase intention from a restaurant was significant. This research offers substantial data for the restaurant managers to be aware about which criteria meet the expectation of the tourists’ in order to attract their restaurant services in a consistent and attractive manner. This research also contributes to the existing knowledge of tourism study by focusing on the restaurant sectors of Malaysia.